The Influence Of Company Size, Liquidity, Profitability On The Issue Of Going Concern Audit Opinions On Mining Companies Listed On The Indonesia Stock Exchange Year 2017-2020 - Situmorang, Humala; Carolina F. Sembiring; Emerald G. M Tobing (Universitas Kristen Indonesia, 2022)
This study is a study that discusses the factors that influence the issuance of Going Concern Audit Opinions in mining organizations listed on the IDX from 2017-2020. The problem to be studied is the extent to which company size, liquidity and profitability affect the assessment of the business continuity review in the organization. This will be done for one semester, especially in the even semester of the 2021/2022 academic year. The research technique used is special multiple regression such as binary multiple regression using logistic, which is an analytical tool to test the effect of two or more independent variables on the dependent variable using quantitative and categorical data. The results of this study it was found that company size and profitability affect the going concern audit opinion, while liquidity does not affect the going concern audit opinion.Key words: Going Concern Audit Opinion, Company Size, Liquidity, Profitability